Constitution or conflict? - Herschel I. Grossman (Brown University, Department of Economics, 2002)
Constitutional resolution of disputes between constituent groups of a polity avoids the incremental costs of civil conflict. But, the political process prescribed by a constitution provides a viable alternative to civil conflict if and only if the constitution is self enforcing. This paper presents theoretical and historical analyses of the possibility of designing a selfenforcing constitution. The theoretical analysis reveals that the following factors make it possible to design a self-enforcing constitution that a polity can use to resolve a given dispute: - No party to the dispute has a big advantage in civil conflict. - The parties to the dispute expect the incremental costs of civil conflict to be large relative to the importance of the dispute. - The parties to the dispute have almost as much concern for the future consequences of the choices that they make as for the current consequences. The theoretical analysis also reveals that a self-enforcing constitution can require limitations on the prerogatives of winners of constitutional contests such that the outcomes of constitutional contests do not matter too much. The historical analysis illustrates the relevance of the theoretical analysis by applying these theoretical results to two dramatic examples of constitutional failure: the secession of eleven Southern states from the Union in 1861 and the National Socialist revolution in Germany in 1933.
Keywords: D7; 330; Self-Enforcing Constitution; Civil Conflict; Secession; National Socialist Revolution; Verfassungsökonomik; Theorie